Transformative Learning Method for Indonesian Language Using Digital Literacy Perspective (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the implementation of digital literacy-based transformative learning in teaching Indonesian language and literature, with a focus on the shift from conventional methods (lectures, memorization) to a more interactive and technology-oriented approach. Through a literature review method with a qualitative approach, this study examines various digital platforms and strategies, including interactive e-learning (Ruang Guru, Quizizz), virtual classes (Zoom, Google Meet), online collaboration (Google Docs, Instagram), gamification (Kahoot!, ClassDojo), and AI-based adaptive technology (Squirrel AI). The results of the study indicate that these methods not only increase active participation, learning motivation, and learning personalization, but also develop skills such as critical thinking, creativity, and collaboration. However, challenges such as the digital divide (limited internet access, lack of understanding of digital literacy in remote areas) hinder optimal implementation. This study recommends strengthening digital infrastructure, teacher training, and developing hybrid models to reach all levels of society. Overall, the transformation of learning through digital literacy has proven to be able to create a more meaningful and relevant learning experience with the demands of the digital era, while maintaining the pedagogical essence in language and literature education.